Survival and safety after neoadjuvant chemotherapy or upfront surgery for locally advanced colon cancer: meta-analysis - Aliseda, Daniel; Arredondo, Jorge; Sánchez-Justicia, Carlos; Alvarellos, Alicia; Rodríguez, Javier; Matos, Ignacio; Rotellar, Fernando; Baixauli, Jorge; Pastor, Carlos (British journal of surgery, 2024)
Abstract Background Neoadjuvant chemotherapy is increasingly used to treat locally advanced (T3–4 Nx–2 M0) colon cancer due to its potential advantages over the standard approach of upfront surgery. The primary objective of this systematic review and meta-analysis was to analyse data from comparative studies to assess the impact of neoadjuvant chemotherapy on oncological outcomes. Methods A systematic review was conducted by searching the MEDLINE and Scopus databases. The search encompassed RCTs, propensity score-matched studies, and controlled prospective studies published up to 1 April 2023. As a primary objective, overall survival and disease-free survival were compared. As a secondary objective, perioperative morbidity, mortality, and complete resection were compared using the DerSimonian and Laird models. Results A total of seven studies comprising a total of 2120 patients were included. Neoadjuvant chemotherapy was associated with a reduction in the hazard of recurrence (HR 0.73, 95% c.i. 0.59 to 0.90; P = 0.003) and death (HR 0.67, 95% c.i. 0.54 to 0.83; P < 0.001) compared with upfront surgery. Additionally, neoadjuvant chemotherapy was significantly associated with higher 5-year overall survival (79.9% versus 72.6%; P < 0.001) and disease-free survival (73.1% versus 64.5%; P = 0.028) rates. No significant differences were observed in perioperative mortality (OR 0.97, 95% c.i. 0.28 to 3.33), overall complications (OR 0.95, 95% c.i. 0.77 to 1.16), or anastomotic leakage/intra-abdominal abscess (OR 0.88, 95% c.i. 0.60 to 1.29). However, neoadjuvant chemotherapy was associated with a lower risk of incomplete resection (OR 0.70, 95% c.i. 0.49 to 0.99). Conclusion Neoadjuvant chemotherapy is associated with a reduced hazard of recurrence and death, as well as improved overall survival and disease-free survival rates, compared with upfront surgery in patients with locally advanced colon cancer. This systematic review and meta-analysis of seven studies involving 2120 patients with locally advanced colon cancer found that neoadjuvant chemotherapy is associated with a reduced hazard of recurrence and death, as well as improved 5-year overall survival and disease-free survival rates, compared with upfront surgery. No significant differences in perioperative complications or mortality were found, but neoadjuvant chemotherapy decreased the risk of incomplete resection. In conclusion, neoadjuvant chemotherapy appears to offer oncological benefits in the treatment of locally advanced colon cancer. Lay Summary Colon cancer is a common medical condition, the established treatment for which involves surgical resection followed by chemotherapy. However, a contemporary shift has led to the investigation of an alternative treatment sequence known as neoadjuvant chemotherapy, wherein chemotherapy precedes the surgery. This study critically assesses the efficacy of neoadjuvant chemotherapy compared with the standard treatment approach of surgery followed by chemotherapy. A systematic review of medical databases was undertaken to identify pertinent research publications on this subject matter. In total, seven studies encompassing data from 2120 patients were included in the analysis. Employing a meta-analysis methodology to synthesize the collective data from these studies, it was revealed that neoadjuvant chemotherapy was linked to higher rates of 5-year overall survival and disease-free survival, alongside a diminished hazard of both recurrence and death. Furthermore, no discernible differences in surgical complications or perioperative mortality were evident across the compared approaches.